1982
DOI: 10.1128/jvi.44.1.344-355.1982
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins of herpes simplex virus type 2 as defined by monoclonal antibodies

Abstract: We used monoclonal antibodies reacting with glycoproteins specified by herpes simplex virus type 2 (HSV-2) to characterize the individual antigens in terms of structure, processing, and kinetics of synthesis in BHK or Vero infected cells. Our results provided a direct demonstration of the structural identity of the gA and gB proteins of HSV-2 as well as confirmation of the existence of type-specific and type-common domains within the gD molecule. They also show that, with the exception of gC, processing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…Previous studies demonstrated that monoclonal antibodies directed against herpes simplex virus types 1 and 2 (2,3,32,34,54), human cytomegalovirus (33), Epstein-Barr virus (46), varicella-zoster virus (15,27), and pseudorabiesvirus (18) can precipitate several polypeptides with different electrophoretic mobilities. Because a similar phenomenon occurred with BHV-1, several approaches were used to analyze the relationships among those BHV-1 glycoproteins that appeared to be complexed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that monoclonal antibodies directed against herpes simplex virus types 1 and 2 (2,3,32,34,54), human cytomegalovirus (33), Epstein-Barr virus (46), varicella-zoster virus (15,27), and pseudorabiesvirus (18) can precipitate several polypeptides with different electrophoretic mobilities. Because a similar phenomenon occurred with BHV-1, several approaches were used to analyze the relationships among those BHV-1 glycoproteins that appeared to be complexed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus these reports have, for the most part, had to use at least two or more antibodies for both HSV-1 and HSV-2. The added complication of the host cell's glycosylation machinery has led us to seek other markers besides those for the major glycoproteins [Pereira et al, 1981[Pereira et al, , 1982Goldstein et al, 1983;Balachandran et al, 1982a;Peterson et al, 1983;Nilheden et al, 19831. While still not characterized, the late emergence of the antigens after infection, their occurrence on the unenveloped purified nucleocapsid, and the predominant speckled nuclear immunofluorescent patterns argue strongly against either antibody's being one of the major glycoproteins even though the tentative molecular weight is consistent with gC (HSV-1) or gA/B [Balachandran et al, 1982al. Which late HSV protein has such specificity is an open question.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the hybridoma techniques of Kohler and Milstein [ 19751 monoclonal antibodies have been prepared which appear to selectively react with HSV-1, HSV-2, or both HSV-1 and HSV-2 [Zweig et al, 1979;Pereira et al, 1980;Killington et al, 1981;Goldstein et al, 1983;Howes et al, 1979;Balachandran et al, 1979. These antibodies have been used to extract labeled virus proteins from infected cells and for fluorescent antibody visualization of the HSV-associated proteins in infected cells [Balachandran et al, 1982al.…”
Section: Introductionmentioning
confidence: 99%
“…In another study with intertypic recombinant viruses (20), an HSV-2 glycoprotein of 63,000 daltons with no apparent HSV-1 counterpart was mapped between 0.55 and 0.65 m.u. Monoclonal antibodies (MABs) to HSV-2 glycoproteins also detected a small glycoprotein with a molecular weight of 60,000 which could be chased into higher-molecular-weight forms of 66,000 and 79,000 (3,4) and was designated gF. Results from two studies with monoclonal antibodies (44,45) showed that HSV-2 gF shared antigenic determinants with HSV-1 gC.…”
mentioning
confidence: 99%